Investigation on the wear behaviour and properties of RHA reinforced 7075 aluminium t6 composites produced by vacuum infiltration - Tanis, Naci Arda; Okur, Onur; Jafaar, Che Nor Aiza; Mohamed Ariff, Azmah Hanim; Recep, Çalin (Universiti Putra Malaysia, 2022)
Aluminum matrix composites containing hard ceramic particles have higher strength, hardness and wear resistance than conventional materials. However, the high cost of hard ceramic reinforcements has led researchers to obtain ceramic reinforcement from organic wastes such as rice husk and eggshell, and they are looking for ways to increase the hardness and wear properties by reinforced these organic wastes. In this study, 1, 2, and 4 vol.% rice husk ash (RHA) were added to AA7075 metal matrix. Samples were produced in a steel tube under 550 mmHg vacuum at 750 °C for 3 minutes. T6heat treatment (aging) was applied to the samples. The density, porosity, and hardness of non-aged and aged samples were measured and compared. In addition, SEM and EDS analysis of aged samples were performed and wear properties under 20 N load was investigated. While the hardness and the porosity of T6 heat treated composites increased with increasing reinforcement volume ratio, T6 heat treatment did not improve the hardness and the wear properties of the composites significantly compared to unreinforced (0 vol%) sample. Wear tests showed that the mass loss increased with the increment of reinforcement-volume ratio. Increasing RHA content resulted in worsening the wear behavior of composites because of the poor wettability of RHA particles.